Screening for new red blood cell alloantibodies after transfusion in patients with sickle cell disease. Issue 8 (17th May 2021) - Rankin, Alexander; Darbari, Deepika; Campbell, Andrew; Webb, Jennifer; Mo, Yunchuan Delores; Jacquot, Cyril; Delaney, Meghan; Luban, Naomi L. C.; Nickel, Robert Sheppard
Abstract: Background: Patients with sickle cell disease (SCD) are frequent recipients of red blood cell (RBC) transfusions and are at risk for RBC alloimmunization. RBC alloimmunization is diagnosed by identifying RBC alloantibodies as part of pre‐transfusion testing, but this testing fails to detect alloantibodies that have evanesced. It may be beneficial to screen for new RBC alloantibody development after transfusion before possible antibody evanescence. Study Design and Methods: Our institution started a new initiative for episodically transfused patients with SCD to obtain at least one antibody screen 2–6 months after transfusion as part of their clinical care. A database was created to prospectively track all transfused patients for 1 year and their post‐transfusion antibody screen results. Patients received prophylactically CEK‐matched RBC units. Results: During the study year, 138 patients with SCD received a total of 242 RBC transfusions. Patients with a history of an RBC alloantibody ( n  = 13, 9.4%) had previously received more RBC units than non alloimmunized patients (median 11 vs. 2 RBC units, p  = .0002). A total of 337 post‐transfusion antibody screens were obtained in 127 patients (92.0%) with 110 patients (79.7%) having at least one antibody screen 2–6 months post‐transfusion. With this prospective testing, two new RBC alloantibodies (anti‐C and ‐M) were identified in two patients. Conclusion: It is feasible to test for new RBC alloantibody development in most episodically transfused patients with SCD as part of their routine care. The yield of this screening appears low with CEK matching, but it could still provide important information for individual patients. Abstract : See editorial on page 2219–2222,  in this issue